ALGORITHM FOR MODELING IMPEDANCE SIGNAL CONVERTERS FOR SENSOR DEVICES - BARYLO, HRYHORII; PAVLENKO, MYKHAILO; ADAMIAK, OLEH; NYKON, OLEH; SOROKA, VLADYSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This study focuses on the development and application of a SPICE modeling algorithm designed for impedance spectroscopy circuits. Impedance spectroscopy is a method widely utilized in sensor technologies and data fusion systems to measure and analyze complex electrical properties. The paper emphasizes the need for advanced modeling techniques that improve the accuracy and reliability of signal conversion in sensor networks and mixed-signal electronics. The developed algorithm leverages modern SPICE macromodels, such as the Differentiator Macro, Multiplier Macro, and Integrator Macro, to simulate active (ZRE) and reactive (ZIM) components of impedance with high precision. These components are crucial for analyzing Nyquist diagrams, which graphically represent impedance in the complex plane. The proposed modeling approach addresses key challenges in impedance measurement, including frequency modulation and the influence of circuit component parameters on signal characteristics. By employing parametric analysis, the algorithm enables researchers to investigate the impact of operational amplifier Gain Bandwidth (GBW) and other critical parameters on the accuracy of impedance measurement. The study presents practical examples demonstrating the algorithm’s application to a quadrature detector—a key element in impedance conversion circuits. Results indicate that signal conversion accuracy significantly improves with GBW values of operational amplifiers exceeding 1E7 Hz, underscoring the importance of selecting high-quality components for circuit design. The versatility of the algorithm lies in its ability to simulate a broad range of operational conditions and to optimize circuit performance by adjusting component specifications. This capability is particularly relevant in the context of modern sensor systems, where reliability and precision are paramount. The findings contribute to the field of mixed-signal electronics, providing a robust framework for analyzing and designing advanced impedance spectroscopy circuits. This research paves the way for further innovations in sensor technology and data fusion systems, where accurate impedance measurement is essential for achieving high-performance functionality.